Right ventricular outflow tract stenting for late presenter unrepaired Fallot physiology: a single-center experience - Prakoso, Radityo; Kurniawati, Yovi; Siagian, Sisca Natalia; Sembiring, Aditya Agita; Sakti, Damba Dwisepto Aulia; Mendel, Brian; Pratiwi, Indah; Lelya, Olfi; Lilyasari, Oktavia (Frontiers in Cardiovascular Medicine, 2024)
Objectives The purpose of this study was to assess the clinical outcome after right ventricular outflow tract (RVOT) stenting in late presenter patient with unrepaired Fallot physiology. Background In younger patients, RVOT stenting is an alternative to mBTT shunt; however, there have been few reports of this palliative technique in late presenter population, including adults. Methods This was a single-center, retrospective study of nonrandomized, palliated Fallot patients. Clinical outcomes such as left ventricular ejection fraction and saturation were measured in 32 individuals following RVOT stenting in adults (n = 10) and children (n = 22). The Statistical Package for Social Science (SPSS) 26.0 software was used to analyze the statistical data. Results During the procedure, the average stent diameter and length were 8.84 ± 1.64 mm and 35.46 ± 11.23 mm, respectively. Adult patients received slightly longer stents than pediatric patients (43.60 ± 11.64 mm vs. 31.77 ± 9.07 mm). Overall, patients' saturation increased from 58.56 ± 19.03% to 91.03 ± 8.98% (p < 0.001), as did their left ventricular ejection fraction (LVEF) from 64.00 ± 18.21% to 75.09 ± 12.98% (p = 0.001). Three patients improved their LVEF from 31 to 55%, 31 to 67%, and 26 to 50%. The median length of stay was 8 (2–35) days, with an ICU stay of 2 (0–30) days. The median time from RVOT stent palliation to total repair was 3 months (range: 1 month–12 months). Conclusions RVOT stenting is a safe and effective method for increasing saturation and ejection fraction not only in newborn infants but also in late presenters, including adults with unrepaired Fallot physiology.